Effects of velocity-based resistance training on young soccer players of different ages - González-Badillo, J. J.; Pareja-Blanco, F.; Rodriguez-Rosell, D.; Abad-Herencia, J. L.; del Ojo-López, J. J.; Sánchez-Medina, L. (The Journal of Strength and Conditioning Research, 2015)
This study aimed to analyze the effect of velocity-based resistance training (RT) with moderate loads and few repetitions per set combined with jumps and sprints on physical performance in young soccer players of different ages. A total of 44 elite youth soccer players belonging to 3 teams participated in this study: an under-16 team (U16, n = 17) and an under-18 team (U18, n = 16) performed maximal velocity RT program for 26 weeks in addition to typical soccer training, whereas an under-21 team (U21, n = 11) did not perform RT. Before and after the training program, all players performed 20-m running sprint (T20), countermovement jump (CMJ), a progressive isoinertial loading test in squat to determine the load that elicited a ~1 m/s velocity (V1LOAD) and an incremental field test to determine maximal aerobic speed (MAS). U16 showed significantly (p = 0.000) greater gains in V1LOAD than U18 and U21 (100/0/0%). Only U16 showed significantly (p = 0.01) greater gains than U21 (99/1/0%) in CMJ height. U18 obtained a likely better effect on CMJ performance than U21 (89/10/1%). The beneficial effects on T20 between groups were unclear. U16 showed a likely better effect on MAS than U21 (80/17/3%), whereas the rest of comparisons were unclear. The changes in CMJ correlated with the changes in T20 (r = -0.49) and V1LOAD (r = 0.40). In conclusion, velocity-based RT with moderate load and few repetitions per set seems to be an adequate method to improve physical performance in young soccer players.